Mix Ingredient Skewer Enterprise: household appliances / Muhammad Danial Faiz Rosman, Mohamad Fitri Amar Mohd Nazri, Asyraf Abdul Rahim, Ikmal Hisham Zainol, Mohamad hafsham Mazlan - Rosman, Muhammad Danial Faiz; Mohd Nazri, Mohamad Fitri Amar; Abdul Rahim, Asyraf; Zainol, Ikmal Hisham; Mazlan, Mohamad hafsham (2016)
As for the business, we are providing an efficient, portable, and user friendly products especially for the Malaysian. Nowadays, people who are preparing meals such as BBQ and Satay usually having a difficult time to prepare the menu especially in large quantity.